The Influence of Advertising at the Point-of-Purchase on Shoppers and Brands: An Empirical Study in Convenience Stores - Silveira, Paulo Duarte; Marreiros, Cristina (Communication Today, 2023)
The main purpose of this research is to understand the influence of shopper marketing and visual brand advertising at the point-of-purchase (PoP) on shopper behaviour and on the retailers-manufacturers relationship, particularly at small retail stores. Two related studies were conducted, with an integrated mixed methods approach. The first, qualitative in nature, used several samples with different purposes. Firstly, a sample of shopper marketing experts, aiming to characterise the shopper marketing approach and the strategic role of PoP advertising. This phase served as the main input for the subsequent phases of the study. The next sample was composed of retailers and manufacturers, with the purpose of understanding their perspectives on the role of brands’ visual advertising at convenience stores. The following study had a similar purpose but utilised a quantitative methodology, with 300 face-to-face interviews with shoppers at convenience stores. Globally, it was found that brands’ visual advertising at the PoP is a way for manufacturers to add value to their relationship with retailers, as well as a tool to increase sales for both parties. It was also found that only the brands’ primary visual advertisements at the PoP influence (some) elements of shopping experience, increase brand awareness and unplanned purchases. This research analyses different actors and samples on the shopper marketing field, thereby extending previous research. Another novelty of the research is that it was focused on convenience stores and was not directed to a single product or category, providing findings from a real shopping environment and on a type of store other than large supermarkets.